Homelessness and Crime: Do Your Friends Matter?1. (14th July 2016) - Corno, Lucia
Abstract : This article investigates the influence of friends on crime, using data I collected among the homeless. To estimate the causal effects of friends and of the share of criminal friends on crime, I rely on two instruments. The first is the share of rainy days during one's first year as homeless: rainfall fosters homeless concentration in sheltered places and increases the probability of interactions. The second is the share of inmates released during one's first year as homeless, which affects the supply of criminal friends. I find that one additional friend decreases the probability of incarceration but criminal friends increases it.